Can CANVA Application be as a English Learning Media? - Marhamah, Marhamah; Yulianto, Yulianto; Salman, Nola Fibriyani Bte (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2023)
Learning media plays a crucial role in the learning process. One of the popular learning media, which played a crucial role among elementary school students during the COVID-19 pandemic, is audio-visual media. This type of media engages both auditory and visual senses through the utilization of the CANVA application. Therefore, this research aims to develop an English language learning media through the CANVA application in Pekanbaru Elementary School, Indonesia. This research was conducted using the 4D development model, consisting of define, design, develop and disseminate stages. In the define stage, it was found that students still had relatively low learning outcomes, and teachers could not develop creative learning media. Meanwhile, in the design stage, the learning media based on the findings in the definition stage was designed. The learning media was assembled using the CANVA application in the development stage. The product test results in this development stage showed very good results. The media was packaged in CD form and distributed to several elementary school teachers in Pekanbaru to help them teach English.